(untitled) (Bangladesh Journal of Microbiology, 2019)
Aquatic plants are generally considered as breeding grounds for mosquitoes and other harmful vectors of diseases. However, in recent years, some research has been carried out to test their significance as sources of antimicrobial lead molecules. The aim of this research was to study the phytochemical composition of local aquatic plant species and test their antimicrobial effect against selected bacterial strains. Three different aquatic plant samples were collected from a large water body near Dhaka. Ethanol and ethyl acetate extracts of the plant species: Eichhornia crassipes, Pistia stratiotes, and Spirodela polyrrhiza were tested against Staphylococcus aureus, Salmonella typhi, and Lactobacillus spp. Out of the eight different extracts, only the ethyl acetate extracts prepared from Eichhornia crassipes showed significant anti-microbial activity against Staphylococcus aureus and Salmonella typhi. In disk diffusion tests, zone of inhibitions of ethyl acetate extracts of Eichhornia crassipes leaves and stems were 8.00 ± 0.5 mm and 7.83 ± .29 mm respectively. In well diffusion tests, zone of inhibitions of ethyl acetate extracts of Eichhornia crassipes leaves and stems were 18.00 mm and 20.00 mm respectively. Zones of inhibition of ethyl acetate extracts of Eichhornia crassipes stems against Staphylococcus aureus were 7.67 ± 0.29 mm and 12.00 mm respectively in disk and well diffusion tests. Zone of inhibition of ethyl acetate extracts of Spirodela polyrrhiza was 8.17 ± 0.29 mm against Staphylococcus aureus in disk diffusion tests. No extracts showed any antimicrobial potential against Lactobacillus. Phytochemical composition analysis showed the presence of alkaloids, flavonoids, steroids, phenolics, tannins, glycosides, and cardiac glycosides in the different ethanol and ethyl acetate extracts. Tannins were absent in all extracts and saponins were absent in all ethyl acetate extracts. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 7-11